Impact and beneficiaries of blockchain in logistics - Thomas Twenhöven; Moritz Petersen (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: Blockchain in logistics is slowly moving beyond the hype. Against this background, we investigate the current expectations concerning the impact and possible beneficiaries of Blockchain applications in the logistics services industry. Methodology: We conduct an online survey among logistics professionals to understand their expectations regarding specific use cases, potential issues, and general developments. Specifically, we ask the respondents to evaluate impacts and beneficiaries of three actual Blockchain projects from the logistics domain. Findings: We find that industry professionals are still optimistic about Blockchain and expect it to make an impact on both communication effectiveness and costs in the industry. However, we also find that the expected impact and beneficiaries strongly depend on the underlying use case. Originality: While there is a fast-growing body of research on Blockchain in the logistics industry, the specific impacts and beneficiaries of Blockchain usage as they relate to different use cases have received little attention to date.
urn:nbn:de:gbv:830-882.054355; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 004; Blockchain; Logistics; Survey; Use cases